Data-driven approaches to define the upper limit of the intermovement interval of periodic leg movements during sleep. Issue 3 (13th January 2018) - Ferri, Raffaele; Silvani, Alessandro; Rundo, Francesco; Zucconi, Marco; Aricò, Debora; Bruni, Oliviero; Ferini-Strambi, Luigi; Manconi, Mauro
Abstract: Study Objectives: To define statistically the upper limit of the intermovement interval (IMI, the time interval between the onset of consecutive movements) of periodic leg movements during sleep (PLMS). Methods: We computed the IMI distribution of a large sample ( n = 141) of patients with restless legs syndrome (RLS) and analyzed it with two independent approaches, based on fitting either empirical functions or normal and exponential functions to the data. Results: The two fitting approaches consistently pointed to an upper limit of the PLMS IMI in the range between 50 and 60 s. Decreasing the upper limit of PLMS IMI from 90 to 60 s evidently decreased the PLMS index in patients with RLS and control participants; nevertheless, the PLMS index remained significantly higher in RLS vs. control participants. Shifting the upper limit of PLMS IMI to 60 s did not significantly modify the effectiveness of discrimination of PLMS between controls and patients with RLS. Conclusion: These results seem to indicate that a conservative, yet data-driven upper limit for IMI contributing to the PLMS in patients with RLS might be 60 s instead of 90 s, as recommended by the present guidelines.